دراسة تطبيقية حول أثر عناصر المزاحمة في القطاع الصناعي عمى الجودة - دراسة حالة خدمة اوريدو الجزائر - بوبكر ياسين بوبكر ياسين (Finance and Business Economies Review, 2017)
<span dir="ltr" style="left: calc(var(–scale-factor)*63.50px); top: calc(var(–scale-factor)*443.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.971794);" role="presentation">Rivalry in Mobile Service <span dir="ltr" style="left: calc(var(–scale-factor)*172.85px); top: calc(var(–scale-factor)*443.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920409);" role="presentation">Sector among active competitors takes several faces to gain and illustrate the <span dir="ltr" style="left: calc(var(–scale-factor)*50.88px); top: calc(var(–scale-factor)*457.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.900011);" role="presentation">competitiveness, <span dir="ltr" style="left: calc(var(–scale-factor)*124.74px); top: calc(var(–scale-factor)*457.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.895394);" role="presentation">depending <span dir="ltr" style="left: calc(var(–scale-factor)*173.42px); top: calc(var(–scale-factor)*457.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903412);" role="presentation">on <span dir="ltr" style="left: calc(var(–scale-factor)*190.44px); top: calc(var(–scale-factor)*457.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.883056);" role="presentation">plans <span dir="ltr" style="left: calc(var(–scale-factor)*218.51px); top: calc(var(–scale-factor)*457.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.837462);" role="presentation">based <span dir="ltr" style="left: calc(var(–scale-factor)*248.36px); top: calc(var(–scale-factor)*457.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903412);" role="presentation">on <span dir="ltr" style="left: calc(var(–scale-factor)*265.38px); top: calc(var(–scale-factor)*457.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.873747);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*284.57px); top: calc(var(–scale-factor)*457.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.898233);" role="presentation">prices, <span dir="ltr" style="left: calc(var(–scale-factor)*318.02px); top: calc(var(–scale-factor)*457.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917595);" role="presentation">advertising, <span dir="ltr" style="left: calc(var(–scale-factor)*371.97px); top: calc(var(–scale-factor)*457.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.912046);" role="presentation">new <span dir="ltr" style="left: calc(var(–scale-factor)*395.48px); top: calc(var(–scale-factor)*457.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919269);" role="presentation">product <span dir="ltr" style="left: calc(var(–scale-factor)*433.10px); top: calc(var(–scale-factor)*457.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.90391);" role="presentation">development, <span dir="ltr" style="left: calc(var(–scale-factor)*50.88px); top: calc(var(–scale-factor)*470.47px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.949412);" role="presentation">quality,...etc. This goes back to the uncomfortable situation that competitors fee<span dir="ltr" style="left: calc(var(–scale-factor)*382.51px); top: calc(var(–scale-factor)*470.47px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.935301);" role="presentation">ls toward those variables, <span dir="ltr" style="left: calc(var(–scale-factor)*50.88px); top: calc(var(–scale-factor)*483.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929252);" role="presentation">OOREDOO is one of those players who work hardly to be updated to the meant changes, and work also to <span dir="ltr" style="left: calc(var(–scale-factor)*50.88px); top: calc(var(–scale-factor)*501.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907259);" role="presentation">interpret its concern as plenty Appearances, that quality is one of them.